Intermediate-temperature conductivity of B-site doped Na0.5Bi0.5TiO3-based lead-free ferroelectric ceramics. Issue 15 (15th November 2016) - Huang, Jinqiang; Zhu, Fangyuan; Huang, Da; Wang, Bing; Xu, Tan; Li, Xiangdong; Fan, Pengyuan; Xia, Feng; Xiao, Jianzhong; Zhang, Haibo
Abstract: Na0.5 Bi0.5 TiO3 (NBT) based oxide-ion conductor ceramics have great potential applications in intermediate-temperature solid oxide fuel cells (SOFCs) and oxygen sensors. Na0.5 Bi0.49 Ti1−x Mgx O3−δ ceramics with x=0, 0.01, 0.02, 0.03, 0.05 and 0.08 were prepared by conventional solid-state reaction. XRD measurement and SEM analysis revealed the formation of pure perovskite structures without secondary phase. MgO doping greatly decreased the sintering temperature and inhibited grain growth. AC impedance spectroscopy measurement was adopted to measure the total conductivity, which was found to increase with MgO doping content ranging from 0 to 3 mol% and subsequently to decrease. High oxygen ionic conductivity σt =0.00629 S/cm was achieved for sample doped with 3 mol% MgO at 600 °C in air atmosphere.